Perfil do professor mediador: estudo de caso nas licenciaturas no IFAM - CMC - Lima, Miriam Bastos Reis Maia (2016)
This study aimed to construct a tool that helps assess the mediator profile. This research is in the line of Formative Processes of Teachers. It deals with research thematic foci of structural, organizational, didactic and pedagogical regarding the formation processes of 56 teachers in technological education institutions, thus considering the impacts and repercussions of the organization of the pedagogical work of the teacher who operates this type of education. It is a quantitative and qualitative research, from a descriptive approach. The theoretical approaches to pedagogy of mediation, the Mediated Learning Experience (MLE) and the mediator profile. The research came from Vygotsky's studies of the Zone of Proximal Development(ZPD), the Feuerstein paradigm concerning the profile of the mediator and cognitive constructivist didactic proposal, whose foci was to identify the educational skills demanded of the teacher as mediator of the teaching / learning process. On these grounds, throughout this study, the author constructed and applied a questionnaire, through which teachers could evaluate their own practice. The demographic profile member of the 36 participants was also part of research to characterize the professionals, their training and teaching practice. Participating teachers work in undergraduate courses in Federal Institute of Education, Science and Technology of Amazonas (IFAM) - Manaus Campus Center (CMC) located in the city of Manaus, state of Amazonas. As methodological procedures, we carried out a quantitative analysis of the facilitator characteristics, through a set of replies to the questionnaire and the analysis of contents of three subjective questions. The ProfMed questionnaire was the product generated by this work. It was noticed, the respondents, appreciation and commitment to the pursuit of continuing education, since the research group presented a high level of mediation as the educational profile: 56% achieved good mediation and 44% good, which is compatible with training and long experience of the teachers participating in the survey. However, it is noteworthy that these results are not expressed by the self-assessment of teachers, given that there was omission of opinion on their performance by 70% of participants. However, through the answers to open questions, teachers demonstrated awareness, commitment and dedication in the performance of their duties.